Incidence, predictors, and clinical outcomes of mechanical circulatory support-related complications in patients with cardiogenic shock. Issue 2 (February 2022) - Takahashi, Kotaro; Kubo, Shunsuke; Ikuta, Akihiro; Osakada, Kohei; Takamatsu, Makoto; Taguchi, Yuya; Ohya, Masanobu; Shimada, Takenobu; Miura, Katsuya; Tada, Takeshi; Tanaka, Hiroyuki; Fuku, Yasushi; et al.
Abstract: Background: Mechanical circulatory support (MCS) is essential to maintain the hemodynamics in selected patients with cardiogenic shock (CS). However, little is known about predictors and clinical impact of device-related complications on clinical outcomes in patients with MCS. Methods: We retrospectively reviewed consecutive 477 patients who received veno-arterial extracorporeal membrane oxygenation (VA-ECMO), Impella (Abiomed, Danvers, MA, USA), and intra-aortic balloon pump (IABP) from January 2012 to May 2020. After excluding patients with only VA-ECMO and patients with MCS for procedural support, 403 patients were included in this study. Predictors and clinical outcomes of device-related complications were analyzed. Furthermore, complication rates were compared between Impella and IABP groups in patients with and without VA-ECMO. Results: Hemolysis, major bleeding defined by Bleeding Academic Research Consortium type 3 or 5 bleeding, thromboembolic events, and ischemic stroke were observed in 42 (10.4%), 150 (37.2%), 52 (12.9%), and 30 patients (7.4%), respectively. Patients with major bleeding had a higher in-hospital mortality than those without major bleeding (31.2% vs. 56.0%, p<0.001), whereas hemolysis (47.6% vs. 52.4%, p=0.32), thromboembolic events (38.5% vs. 40.7%, p=0.76), and ischemic stroke (48.5% vs. 39.7%, p=0.33) did not increase the in-hospital mortality. In multivariate analysis, both Impella and VA-ECMO were independent predictors of major bleeding and thromboembolic events. However, in-hospital mortality was similar between the Impella and IABP groups irrespective of the VA-ECMO insertion. Conclusions: Among several important complications in CS patients with MCS, major bleeding events most strongly affected the mortality. Implanted MCS type was associated with the device-related complications. Graphical abstract: Image, graphical abstract